Epidemiology and characteristics of neurosurgical pathologies in a high complexity Peruvian hospital. Period 2008-2020 - Alarcón-Braga, Esteban A. (2022)
Background: the neurosurgical burden of disease is high worldwide. Information regarding this in Peru is limited. We aim to describe epidemiological characteristics and temporal distribution of the neurosurgical burden of disease in a high complexity center in Peru. Material and Methods: we carried a cross-sectional analytical study using the surgery registry from the neurosurgical department of Hospital Nacional María Auxiliadora in Lima-Peru, which contains registers from 2008 to 2020. Diagnoses were classified into main diagnosis, a variable with 10 levels, each a broad category; and specific diagnosis, defining the etiology. Absolute and relative frequencies were described on a diagnosis basis. Temporal distribution was described using a heatmap. Chi-squared test was used to evaluate association between variables and sex. Results: there were 2948 surgeries in the studied period. The median age was 38, and 66,7% were male. Head trauma, hydrocephalus and vascular pathology represent 60,0% of neurosurgical burden of disease in our center. The most frequent specific diagnoses of head trauma were chronic subdural hematoma (20,2%) and epidural hematoma (19,4%). Reinterventions were 7,4% of all procedures. Sex and principal diagnosis were associated (p < 0.001). Conclusions: The most frequent diagnoses were head trauma, hydrocephalus and vascular pathology. We describe an association between principal diagnosis and sex. There is need for further understanding of the neurosurgical burden of disease in Peru.